Crystal structure, Hirshfeld surface analysis, and DFT and molecular docking studies of 6-cyanonaphthalen-2-yl 4-(benzyloxy)benzoate - Mahadevaiah Harish Kumar; Shivakumar Santhosh Kumar; Hirehalli Chikkegowda Devarajegowda; Hosapalya Thimmaiah Srinivasa; Bandrehalli Siddagangaiah Palakshamurthy (Acta Crystallographica Section E: Crystallographic Communications)
In the title compound, C25H17NO3, the torsion angle associated with the phenyl benzoate group is −173.7 (2)° and that for the benzyloxy group is −174.8 (2)° establishing an anti-type conformation. The dihedral angles between the ten-membered cyanonaphthalene ring and the aromatic ring of the phenyl benzoate and the benzyloxy fragments are 40.70 (10) and 87.51 (11)°, respectively, whereas the dihedral angle between the aromatic phenyl benzoate and the benzyloxy fragments is 72.30 (13)°. In the crystal, the molecules are linked by weak C—H...O interactions forming S(4) chains propagating parallel to [010]. The packing is consolidated by three C—H...π interactions and two π–π stacking interactions between the aromatic rings of naphthalene and phenyl benzoate with centroid-to-centroid distances of 3.9698 (15) and 3.8568 (15) Å, respectively. Intermolecular interactions were quantified using Hirshfeld surface analysis. The molecular structure was further optimized by density functional theory (DFT) at the B3LYP/6–311+ G(d,p) level, revealing that the energy gap between HOMO and LUMO is 3.17 eV. Molecular docking studies were carried out for the title compound as a ligand and SARS-Covid-2(PDB ID:7QF0) protein as a receptor giving a binding affinity of −9.5 kcal mol−1.